INTEGRITY, COURAGE, SCEPTICISM (Analele Universității București.Filosofie, 2025)
Does our inability to always self–attribute epistemic courage when we manifest it (a limited kind of reflective scepticism about epistemic courage) conflict with the virtue of integrity? I articulate this problem, and argue that it can be eschewed if we construe integrity along meliorist rather than perfectionist lines.